Biomechanical evaluation in runners with Achilles tendinopathy (Clinics, 2021)
OBJECTIVES: To evaluate the clinical characteristics, ground reaction force (GRF), and function of the plantar muscles and dorsiflexors of the ankle in runners with and without Achilles tendinopathy (AT) and in nonrunners. METHODS: Seventy-two participants (42 men, 30 women; mean age: 37.3±9.9 years) were enrolled in this crosssectional study and divided into three groups: AT group (ATG, n=24), healthy runners’ group (HRG, n=24), and non-runners’ group (NRG, n=24). Both ankles were evaluated in each group. The American Orthopedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Scale was used for clinical and functional evaluation. GRF was evaluated using force plates and muscle strength was evaluated using an isokinetic dynamometer. RESULTS: The AOFAS scores were lower in the ATG. The strike impulse was higher in the ATG than in the HRG and NRG. However, GRF was similar among the groups. The ATG exhibited lower total work at 120o /s speed than the HRG. The peak torque in concentric dorsiflexion was lower in the NRG than in the ATG and HRG. The peak torque and total work in concentric plantar flexion were lower in the NRG than in the ATG. The peak torque and total work in eccentric plantar flexion were lower in the NRG than in the ATG and HRG. CONCLUSION: Runners with AT showed higher strike impulse, lower muscle strength of the plantar flexors, and higher clinical and functional damage.